Challenges for Low‐Income Children in an Era of Increasing Income Inequality. (6th December 2017) - Odgers, Candice L.; Adler, Nancy E.
Abstract: Children growing up in poverty are at heightened risk for poor health. Researchers have identified some mechanisms responsible for this association but we know less about how children are affected by growing up in communities, schools, and countries with varying levels of income inequality. In this article, we summarize what is known about the association between children's well‐being and income inequality, and outline three challenges that increasing levels of income inequality may pose to children from low‐income families. We also discuss implications for research and policy.